Apoyo en la oficina de infraestructura de la alcaldía mayor de Tunja Boyacá. (2023)
This business practice report when carried out in the municipality of Tunja Boyacá in the infrastructure secretary supporting activities and Civil Work(s) Contracted and Executed by the Administration in order to cover the needs, the intern manages to support the activities as was the review of technical documentation of the different contracts and delivery of reports on the completion of works carried out by the mayor's office and adjustment of the same according to the requirements of the infrastructure office, obtaining better results in carrying out bidding processes on the other hand support was provided in carrying out technical visits and activities carried out in the infrastructure office, improving their prompt responses by applying the knowledge obtained during the training process in the civil engineering program of the Antonio Nariño Duitama University; With the help of the supervisors in charge and with the documentation and established norms such as the Colombian Regulation for arthquake Resistant Construction (NSR-10) and the Unit Price Analysis (APU) of the Boyacá government, it is possible to collect the necessary information. for each assigned activity, the rocessing and determination of results, managing to contribute with the realization of an Excel format for the delivery of work reports where it is made available to the infrastructure secretary suggesting to the mayor's office the planning of a schedule with the activities to be carried out.